Design of Portable Reflectivity Test Probe. Issue 4 (June 2019) - Ping, Wei; Lewu, Deng; Lei, Zhang; Peng, Cui
Abstract: This paper introduced the design of a portable probe which can measure the reflectivity of the surface radar stealth coating. By using swallowing pulse in the design of variable frequency division phase-locked frequency synthesis technology to microwave circuit, automatic control circuit and the H horn probe integration, solve the rigid connection deformations of RF cable and adapter vulnerability caused by the phase and impact the measuring accuracy of standing wave change. With the special design of the new probe, it has the characteristics of high stability, good repeatability, small effect of environmental temperature, excellent reliability and automation.